Wavelength conversion and temporal compression of pulse train using dispersion oscillating fibre. Issue 10 (1st May 2014) - Feng, F.; Fatome, J.; Sysoliatin, A.; Chembo, Y.K.; Wabnitz, S.; Finot, C.
Abstract : The generation of a picosecond pulse train is demonstrated taking advantage of the cross‐gain occurring in a dispersion‐oscillating fibre. The resulting frequency‐converted signal is detuned by more than 20 nm from the pump and can be temporally compressed by a factor of 2 compared with the input sinusoidal pump wave.